CEIDP '05. 2005 Annual Report Conference on Electrical Insulation and Dielectric Phenomena, 2005.
DOI: 10.1109/ceidp.2005.1560771
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectricity in multi-air voids electrets

Abstract: Multi-air voids space-charge electrets have been developed using two fluorethylenepropylene (Teflon-FEP) films. In this work, a new technique developed to assembler these films allows the control of the thickness and shapes of multi-air voids distributed on their surface. When an impulse voltage process charges these voids, it is possible to obtain samples with high piezoelectric coefficients. To explain this piezoelectric characteristic, a theoretical explanation based on the electret microphone mechanism is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…A few years ago, light emission from the internal voids during electrical charging has been reported [4,5]. The light emission indicates internal electric discharges which can also be investigated on the recently developed polymeric layer structures with welldefined voids [6,7]. Experimental results have demonstrated that even before the onset of light emissions, the polymer structures already exhibit a significant piezoelectric coefficient that grows linearly with the applied electric field, until electrical discharges begin at certain field strength, and the piezoelectric coefficient reaches saturation [8].…”
Section: Introductionmentioning
confidence: 98%
“…A few years ago, light emission from the internal voids during electrical charging has been reported [4,5]. The light emission indicates internal electric discharges which can also be investigated on the recently developed polymeric layer structures with welldefined voids [6,7]. Experimental results have demonstrated that even before the onset of light emissions, the polymer structures already exhibit a significant piezoelectric coefficient that grows linearly with the applied electric field, until electrical discharges begin at certain field strength, and the piezoelectric coefficient reaches saturation [8].…”
Section: Introductionmentioning
confidence: 98%
“…Even though the double-layer electrets initially exhibited rather high piezoelectric activities, the shellac led to a fast deterioration and to destruction of the samples. Here, we present a new and stable piezoelectret [16] technology with Teflon®-FEP electret films and thermo-formed bubbles in between [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric d 33 coefficients of cellular i-PP up to 1200 pC/N were measured [22]. Recently, several other cellular or layered polymers, such as COC [23,24], PETP [25,26] and FEP/PTFE [27][28][29] were also investigated in relation to piezoelectric activity.…”
Section: Introductionmentioning
confidence: 99%